ANALISIS DAN PERANCANGAN SISTEM INFORMASI SUMBER DAYA MANUSIA MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA PERUSAHAAN OTOMOTIF - ADE KURNIAWAN (Institut Bisnis Muhammadiyah Bekasi, 2021)
In this era of globalization, technology and information systems have an important influence on the development of companies, including the automotive business. In addition to technology and information systems, human resources also play an important role in the success of a company. Therefore, many companies develop information technology and systems to carry out effective human resource management. This study uses the Rapid Application Development (RAD) method, a human resource system developed with an application programming language based on Visual Basic. NET. This application aims to assist companies in managing their employees by recording applicant and employee information, employee submissions, employee attendance, and reports to manage their employees. The application of the human resource information system provides conveniencein carrying out the employee management processIn this era of globalization, technology and information systems have an important influenceon the development of companies, including the automotive business. In addition totechnology and information systems, human resources also play an important role for thesuccess of a company. Therefore, many companies develop information technology andsystems to carry out effective human resource management. This study uses the RapidApplication Development (RAD) method, a human resource system developed with anapplication programming language based on Visual Basic .NET. This application aims toassist companies in managing their employees by recording applicant and employeeinformation, employee submissions, employee attendance, and reports to manage theiremployees. The application of the human resource information system provides conveniencein carrying out the employee management process